Information-energy metasystem model. Issue 8 (7th September 2015) - Last, Cadell
Abstract : Purpose: – The human system is developing into a global biocultural superorganism. However, in the process of aligning a stable global goal state, contemporary human control systems appear to be inadequate structures. The purpose of this paper is to help humanity contextualize the nature of our highest control systems and guide future structural control system decisions, by proposing the application of an Information-Energy Metasystem Model (IEMM). Design/methodology/approach: – IEMM is an evolutionary-cybernetic model built with biological, anthropological, and historical data, and constructed utilizing two cybernetic theories: metasystem transition theory and control information theory (CIT). The IEMM suggests that major control transitions are dependent on specific information-energy control and feedback properties. Findings: – Throughout our evolutionary history humans have stabilized three distinct metasystems in the general organization of bands/tribes stabilized by language-hunting feedback, chiefdoms/kingdoms stabilized by writing-agricultural feedback, and nation-states stabilized by printing press-industrial feedback. In the future, IEMM predicts that new global (or "glocal") controls based on the internet as an information medium, and renewable energy as an engine for stabilization, could potentially generate a fourth metasystem. However, this is largely dependent on our own ability and willingness for fundamental structural control innovation. Originality/value: – This is the first paper to analyze the contemporary control system structure within the context of the whole of human evolution.